2018
DOI: 10.1242/dev.157511
|View full text |Cite
|
Sign up to set email alerts
|

Late neuroprogenitors contribute to normal retinal vascular development in a Hif2a-dependent manner

Abstract: In the adult central nervous system, endothelial and neuronal cells engage in tight cross-talk as key components of the so-called neurovascular unit. Impairment of this important relationship adversely affects tissue homeostasis, as observed in neurodegenerative conditions including Alzheimer's and Parkinson's disease. In development, the influence of neuroprogenitor cells on angiogenesis is poorly understood. Here, we show in mouse that these cells interact intimately with the growing retinal vascular network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 69 publications
3
7
0
Order By: Relevance
“…We also present a genetic analysis of the different roles of Hif-1α and Hif-2α in Müller glia versus neurons in the context of normal versus Norrin-deficient retinal vascular development. These results support and extend those of previous studies (16,17,22,24) and demonstrate that (a) the hypoxia response of retinal neurons is mediated by HIF-1α and is required for development recombination of all 4 alleles is required to generate a defect in retinal vascular development. Although the cortical thinning in Vegf-and Hif-α-KO mice is most simply explained as a secondary effect of hypovascularization, a reduction in glia-derived VEGF could also have a direct effect on the development and survival of cortical neurons (33).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We also present a genetic analysis of the different roles of Hif-1α and Hif-2α in Müller glia versus neurons in the context of normal versus Norrin-deficient retinal vascular development. These results support and extend those of previous studies (16,17,22,24) and demonstrate that (a) the hypoxia response of retinal neurons is mediated by HIF-1α and is required for development recombination of all 4 alleles is required to generate a defect in retinal vascular development. Although the cortical thinning in Vegf-and Hif-α-KO mice is most simply explained as a secondary effect of hypovascularization, a reduction in glia-derived VEGF could also have a direct effect on the development and survival of cortical neurons (33).…”
Section: Resultssupporting
confidence: 91%
“…Distinct roles for HIF-1α and HIF-2α in the development of intraretinal capillaries. HIF-1α and HIF-2α play essential roles in the development of inner plexiform layer (IPL) and outer plexiform layer (OPL) capillaries, respectively (11,16,17). To confirm and extend these observations, we began by quantitatively assessing the vascular phenotypes associated with loss of Hif-1α, Hif-2α, or both Hif-1α and Hif-2α in retinal neurons and Müller glia ( Figure 1, A-C).…”
Section: Resultsmentioning
confidence: 95%
“…VEGF‐A, another HIF‐1α target implicated in angiogenesis and cerebral microvasculature reconstruction during brain recovery, is also more significantly regulated by HIF‐2α in human umbilical vein endothelial cells (Downes et al., 2018) and primary cortical neurons (Ralph et al., 2004). This is in line with the function of HIF‐2α in neurovascular development (Cristante et al., 2018). Chromatin immunoprecipitation (ChIP) studies using cancer (Mole et al., 2009; Smythies et al., 2019) or endothelial cell lines (Bartoszewski et al., 2019) revealed that the two HIFα isoforms have differential but complementary transcriptional regulation (Downes et al., 2018).…”
Section: Discussionsupporting
confidence: 82%
“…Visual deprivation (particularly during the fetal period in mice) or deleting melanopsin ( Opn4 knockout mice) leads to persistence of the hyaloid artery and overgrowth of the retinal vascular plexus. Elevated retinal neuron numbers in dark-reared or Opn4 knockout mice leads to a more hypoxic retina, increased retinal Vegfa production and feedback to the vascular compartment that expresses VEGF receptors (Vegfr2) ( Rao et al, 2013 ; Cristante et al, 2018 ). In addition, RGCs that express another opsin, Opn5 , indirectly regulate vascular development ( Nguyen et al, 2019 ).…”
Section: The Roles Of Rgcs In Retinal Developmentmentioning
confidence: 99%